Capital Mobility and EU Enlargement - Claudia M. Buch (Kiel Institute of World Economics (IfW), 1999)
The EU has recently entered accession talks with five transition economies of eastern Europe. Membership in the EU would require inter alia the full liberalization of capital flows. This paper provides empirical evidence on the openness towards foreign capital that the accession states have attained so far on the basis of the correlation between domestic saving and investment. A comparison with the southern members of the EU shows that the countries under review have reached a similar degree of integration in quantitative terms. Yet, further adjustment in qualitative terms, i.e., in the structure of capital flows, can be expected as the process of accession proceeds.
Keywords: F21; F32; F36; 330; capital mobility; EU enlargement; transition economies; Kapitalmarktliberalisierung; Internationale Kapitalmobilität; EU-Erweiterung; Sparen; Gesamtwirtschaftliche Investitionstheorie; Schätzung; Vergleich; Osteuropa; Südeuropa